Insight into electrochemical passivation behavior and surface chemistry of 2205 duplex stainless steel: effect of tensile elastic stress. (December 2021) - Chen, Longjun; Liu, Wei; Dong, Baojun; Zhao, Yonggang; Zhang, Tianyi; Fan, Yueming; Yang, Weijian
Abstract: The effect of tensile elastic stress on passivation behavior and surface chemistry of 2205 duplex stainless steel is investigated. Elastic stress increases the potential drop at the film/solution interface, donor density and defects diffusion coefficient, resulting in the increase of passive current density. High elastic stress (≥60%σs ) leads to the generation of soluble CrO3, the increase of oxidized Cr and Fe(Ⅱ) content and the decrease of film thickness, resulting in the quasi-steady-state current density no longer independent of potential. Passive film become denser from spontaneous passivation to primary passivation and Fe(III) compounds dominate the passive film under secondary passivation. Highlights: Passivation of 2205 DSS under elastic stress is studied. Elastic stress results in the increase of I ss by decreasing d and increasing φ f / s, N D, and D 0 . High elastic stress (≥60% σs ) leads to further increase of I ss, which is no longer independent of potential. Elastic stress facilitates the increase of oxidized Cr and Fe(Ⅱ) content. Potential makes passive film become denser until transpassivation occurs.